2016
DOI: 10.1155/2016/6802810
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Bowel Preparation for Video Capsule Endoscopy

Abstract: During video capsule endoscopy (VCE), several factors, such as air bubbles, food material in the small bowel, and delayed gastric and small bowel transit time, influence diagnostic yield, small bowel visualization quality, and cecal completion rate. Therefore, bowel preparation before VCE is as essential as bowel preparation before colonoscopy. To date, there have been many comparative studies, consensus, and guidelines regarding different kinds of bowel cleansing agents in bowel preparation for small bowel VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(48 reference statements)
1
16
1
Order By: Relevance
“…Nevertheless, small-bowel preparation with 2L of polyethylene glycol before CE seems to improve the quality of mucosa visualization and the diagnostic yield. There are no differences regarding the CE completion rate, GTT and SBTT (12,33,34). In our study, 41.6% (n = 54) of CE were classified as poor-fair, which may be explained by the enteric preparation used (fasting and a liquid diet the day before the procedure).…”
Section: Discussioncontrasting
confidence: 49%
“…Nevertheless, small-bowel preparation with 2L of polyethylene glycol before CE seems to improve the quality of mucosa visualization and the diagnostic yield. There are no differences regarding the CE completion rate, GTT and SBTT (12,33,34). In our study, 41.6% (n = 54) of CE were classified as poor-fair, which may be explained by the enteric preparation used (fasting and a liquid diet the day before the procedure).…”
Section: Discussioncontrasting
confidence: 49%
“…We opted to examine both 2 and 4 L PEG preparations, given its widespread use in the United States. Some studies have shown that 2 L of PEG may be adequate for small bowel visualization in VCE [26]. However, current guidelines indicate that a full or partial bowel preparation may be used prior to VCE [17]; therefore, we opted to study both a 2 and 4 L PEG bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Korean guidelines released in 2013 stated that preparation with PEG solution enhanced the SBVQ and also DY, but it did not affect the CR . A more recent meta‐analysis and systematic review concluded that preparation with PEG enhanced the SBVQ only, and did not affect the CR or DY. Yung et al .…”
Section: Current Status Of Preparation For Sbcementioning
confidence: 99%